Characteristics Of Minerals With Spectroskopic IR At The Gold Mining Area Of Botak Mountain - Helda Andayany; Josephus Ronny Kelibulin (Jurnal Fisika Indonesia, 2020)
There are three rock samples that have been taken from the gold mining area of Botak mountain. The rock samples were then analyzed with spectroscopic IR to estimate the characteristic of mineral in the area. Analysis results indicate that the type of mineral found in rock samples 2 is dominated by Kaolinite, Organic Carbon, Palygorskite and Quartz. So it can be estimate the type of rock contained in that area is Quartzite. The analysis result of mineral type analysis on rock samples 1 dan 3 have similarities that is Kaolinite, Organic Carbon, Palygorskite, and Albite. So it can be estimate that the other types of rock in the area are Andesite and Limestone. The existence of Andesit and Limestone shows that there has been alteration and hydrothermal mineralization from volcanic origin rock. So it can be estimate that these rocks are the bearing rocks and hosted rocks of base metals and gold. Whereas the quartzite is a bond mineral from gold carrying rocks